THE SPECIFICS OF SUSPENDING PRISON SENTENCES AND THE EXECUTION OF INCARCERATION MEASURES WITH REGARD TO PREGNANCY AND THE PERSONALITY OF A WOMAN - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Women as criminals, who have received prison sentences, have, if certain conditions are met, special rights tied to their reproductive function. This paper highlights the issues women who have received prison sentences face, considering that there is only one institution in the Republic of Serbia in which women serve prison sentences. Special regard will be given to pregnant women expecting the execution of a prison sentence, their right to have the sentence suspended, as well as their right to release on temporary licence. The subject of this paper will also be what is perhaps the most complex issue: the incarceration of pregnant women.